Utilization of Papaya Seed Powder as a Bioadsorben to Reduce Total Iron (Fe) in Wastewater - Munira Munira; Andi Aladin; Perwitasari Perwitasari; Nur Aulia Hamza; St Umrah Tulzhaliza (Eksergi, 2022)
Papaya is a tropical plant that is widely cultivated in Indonesia. Papaya seeds have a high cellulose content, so that papaya seeds can be used as raw material for adsorbents (biosorbents). Biosorbent is used to reduce environmental pollution through the absorption of various types of liquid waste including heavy metals. Fe is an essential heavy metal if in excess amounts can cause toxic effects. One of the methodes to reduce  of iron ion in wastewater is  the adsorption method is using papaya seed biosorbents. The aim of study was to determine the effectivness of using papaya seedd as bioadsorbent  to reduce of iron ion in the wastewater. Papaya seed as the adsorbent agent activated ones was used in five particle size and contact time variations in order to determine the optimum particle size and contact time of papaya seed powder to absorb the heavy metals. The results show that the optimum adsorbent particle size was 100 mesh and the optimum contact time was 60 minute. The adsorption efficiency of (Fe) metal ions in wastewater was 60%, the adsorption capacity value was 0.365 mg/g.  Kinetic modelling of adsorption process is  pseudo second order.